PENGARUH MANAJEMEN ASET DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR KERAMIK, PORSELEN DAN KACA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Arshandy, Eliza; Lie, Darwin; Jubi, Jubi; Ervina, Nelly (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2018)
The purpose of this research is to know the description of asset management, capital structure and profitability and the influence of asset management and capital structure on profitability at Firm in Sub-Sector Keramik, Porselen dan Kaca listed on the Indonesia Stock Exchange. The research design is a library research. The analysis data technique is: assumption classic test, qualitative and quantitative descriptive analysisThe result is Å¶ = -0,044+ 0,072X1 + 0,013X2. Correlation coefficient = 0,788 and RSquare 0,622. Simultaneous test results obtained Fcount>Ftable (18,079>3,44) or significance level obtained 0,000<0,05 means management and capital structure has significant effect on profitability at Firm in Sub-Sector Keramik, Porselen dan Kaca listed on the Indonesian Stock Exchange. The t-test for asset management shown tcount>ttable (4,911>2,073) or significance level is 0,000<0,05 means asset management has insignificant effect on the profitability at Firm in Sub-Sector Keramik, Porselen dan Kaca listed on the Indonesian Stock Exchange. The t-test for capital structure shown tcount<ttable (-1,421<2,073) or significance level is 0,169>0,05 means capital structure has insignificant effect on profitability at Firm in Sub-Sector Keramik, Porselen dan Kaca listed on the Indonesian Stock Exchange.The result of this research suggests the Company should not adding to much assets if that not increased in sales and also optimize the use of debt and the company seeks credition with lower interest rate.Â Keywords: management, capital structure and profitability